Characterization of sucrose binding protein as a seed-specific promoter in transgenic tobacco Nicotiana tabacum L. - Nasibeh Chenarani; Abbasali Emamjomeh; Hassan Rahnama; Katayoun Zamani; Mahmoud Solouki (PLoS ONE)
Seed-specific expression using appropriate promoters is a recommended strategy for the efficiently producing valuable metabolites in transgenic plants. In the present study, we investigated the sequence of sucrose binding protein (SBP) as a seed-specific promoter to find the cis-acting elements specific to gene expression in seeds. The 1860 bp SBP sequence was analyzed using Plant Care and PLACE databases to find cis-acting elements, which resulted in a finding of 22 cis-acting elements required for seed expression. In addition, we have discovered cis- acting elements that are indirectly involved in triacylglycerol synthesis (GATABOX, DOFCOREZM, CACGTGMOTIF). The seed specificity of SBP was analyzed by generating a stable transgenic tobacco plant harboring β-glucuronidase (GUS) reporter gene under the control of the SBP promoter. Histochemical analysis of these transgenic tobacco plants indicated decreasing GUS activity in the leaves during the vegetative stage. However, the mature seeds of transgenic plants showed GUS activity. Moreover, the SBP promoter function in the seed oil content was evaluated by the expression of DGAT1. The expression analysis of DGAT1 in SBP-DGAT1 transgenic tobacco seeds using quantitative real-time PCR revealed a 7.8-fold increase in DGAT1 than in non-transgenic plants. Moreover, oil content increased up to 2.19 times more than in non-transgenic plants. And the oil content of the SBP-DGAT1 transgenic tobacco leaves did not change compared to the control plant. Therefore, we suggested that the SBP promoter could be used as a seed-specific promoter for targeted expression of desired genes in the metabolite engineering of oilseed crops.